KONSEP DAN STRATEGI MENCIPTAKAN PENDIDIKAN KARAKTER DI MADRASAH - Najib Mohamad; Dahari Dahari; Mohamad Maulidin Alif Utama (STAI Asy-Syukriyyah, 2021)
The Purpose This Research is to Describe Strategies to create character education in madrasas. As a party organizing education, both the government and the private sector. Therefore, collaboration between the school and family is a must. In other side, schools must also be able to create the character of education. The Method use library research with reference search efforts literature related to the subject matter discussed descriptively. In creating character education in schools, there are several things that must be done. First thing first is the formulation of a vision, mission and quality targets that can be understood by all parties, be it leaders, teachers, employees, students, parents and school or madrasah committees. The second is to have a strong leadership spirit, to get support and connections from all related advice. The third one has the motivation to excel in this globalization era. The fourth one strives for consistent training and development of teaching staff. The fifth is evaluation of learning outcomes and looking for the root of the problem to make learning even better. The sixth always communicates with the parents, guardians and the local community. The seventh one is building a good network of cooperation with related parties continuously. Keywords: Strategies, character of education, madrasas.